DNA Memethylation Agents Promote Pancreatic Endodermal Differentiation of Mesenchymal Stem Cells. (July 2018) - Sivanathan, Kisha; Manaph, Nimshitha Pavathuparambil Abdul; Nitschke, Jodie; Drogemuller, Chris; Zhou, Xin-Fu; Coates, Patrick T.
Abstract : Background: Adult mesenchymal stem cells (MSC) are a promising avenue to generate insulin-secreting beta cells to replace the need for large numbers of human islets required for transplantation. In this preliminary study, we aim to induce the expression of endodermal markers FoxA2 and Sox17 in MSC by priming them with demethylation agents as a strategy to enhance MSC efficiency to differentiation into insulin-secreting beta cells. Methods: Human bone marrow derived MSC were isolated and cultured from 3 healthy donors. MSC were either untreated (untreated-MSC) or primed with demethylating agents Rg108 (MSC-Rg108) or 5-Azacytidine (MSC-5-Aza) for 18 hours. These cells were then induced to differentiate into definite-endodermal like cells for 5, 7 or 11 days. The immunophenotype of untreated-MSC, MSC-Rg108 and MSC-5-Aza was characterised based on the cell surface expression of standard MSC markers by flow cytometry. The expression of other mesenchymal or endodermal like proteins (eg. Vimentin, Sox17, FoxA2) was determined by immunofluorescence or real-time PCR. Results: Immunophenotype of MSC-Rg108 or MSC-5-Aza was similar to untreated-MSC. Greater than 90% MSC were positive for CD44, CD73, CD90, CD105 and MHC class I. The expression levels of these standard MSC markers were also similar in all MSC groups. All MSC cultures were negative for CD14 and MHC class II. The expression of the mesenchymal cell marker Vimentin was detected at similar levels in the untreated and 18 hours demethylation agent primed MSC groups. Sox17 and FoxA2 expression was induced in untreated-MSC, MSC-Rg108 and MSC-5-Aza when these cells were differentiated into pancreatic endodermal cells. MSC-Rg108 and MSC-5-Aza showed a 3- and 16-fold increase of Sox17 mRNA transcript levels respectively compared to untreated-MSC as early as day 5 of endoderm induction. Robust nuclear expression of Sox17 protein was also detected at days 5, 7 and 11 of endodermal induction in all the MSC groups. Nuclear and cytoplasmic expression of FoxA2 was evident in the untreated-MSC, MSC-Rg108 and MSC-5-Aza at days 7 and 11 of endodermal induction. Interestingly, we observed the formation of islet-like clusters as early as day 7 of endoderm induction in the demethylation agent primed MSC groups but not in untreated-MSC. Conclusion: Priming MSC with DNA demethylation agents can promote MSC efficiency to differentiate into endodermal like cells. We are currently comparing the differentiation efficiency of untreated-MSC, MSC-Rg108 and MSC-5-Aza to form pancreatic precursor cells and insulin-secreting beta cells. Funding for this project is supported by the Cooperative Research Centre for Cell Therapy and Manufacturing (CRC-CTM), Australia.